Mini Review: The Forensic Value of Heat Shock Proteins - Prangenberg, Julian; Doberentz, Elke; Mawick, Anthea; Madea, Burkhard (Frontiers in Medicine, 2022)
Forensic pathologists are routinely confronted with unclear causes of death or related findings. In some instances, difficulties arise in relation to questions posed by criminal investigators or prosecutors. Such scenarios may include questions about wound vitality or cause of death where typical or landmark findings are difficult to ascertain. In addition to the usual examinations required to clarify unclear causes of death or address specific questions, immunohistochemistry and genetic analyses have become increasingly important techniques in this area since their establishment last century. Since then, many studies have determined the usefulness and significance of immunohistochemical and genetic investigations on cellular structures and proteins. For example, these proteins include heat shock proteins (Hsp), which were first described in 1962 and are so called based on their molecular weight. They predominantly act as molecular chaperones with cytoprotective functions that support cell survival under (sub) lethal conditions. They are expressed in specific cellular compartments and have many divergent functions. Central family members include, Hsp 27, 60 and 70. This mini review investigates recent research on the Hsp family, their application range, respective forensic importance, and current limitations and provides an outlook on possible applications within forensic science.